Crystal growth, structural, optical, thermal, dielectric, mechanical and NLO studies of L-tyrosine zinc carbonate single crystals. (2022) - Aishwarya, P.; Ilango, E.; Ramalingam, G.; Vetrivelan, V.
Highlights: Higher SHG of LTZC has been found 2.12 times that of same particle size of KDP. Higher thermal stability and low dielectric loss. XRD was carried out, it showed that the grown crystal possess high crystalline nature. Morphology of the grown crystal was analyzed. Dielectric properties of the LTZC crystal were discussed. Abstract: L-Tyrosine Zinc Carbonate (LTZC) a semi-organic nonlinear optical single crystal has been grown by slow evaporation solution technique. The lattice parameters of the grown crystals are found out by single crystals X- ray diffraction technique. The modes of vibrations of different functional groups present were identified by using Fourier Transform Infrared (FTIR) spectroscopic analysis. The UV–Visible optical absorption spectrum shows that the crystal has high transmission with lowest UV cutoff wavelength of 230 nm. The calculated band gap of LTZC crystal was found to be 5.13 eV. Dielectric constant and dielectric loss for various frequencies and temperatures were performed on LTZC crystal and the results were discussed in detail. The frequency dependence of ac conductivity for different temperatures was studied. The photoconductivity studies confirm that the crystal LTZC has negative photo conducting nature. The mechanical and thermal properties of the grown crystals have been studied. Surface morphological changes are observed in the grown LTZC crystal. The Non-linear optical second harmonic generation conversion efficiency of LTZC was determined using Q-switched Nd: YAG laser. The second harmonic generation conversion efficiency of LTZC is 2.12 times that of KDP.